Myocarditis and pericarditis in young patients following Campylobacter jejuni enterocolitis infection: a systematic review of case studies - Katharine Sanicola; Nikita Shadani; Eric C. Nemec; Suzanne J. Rose (Journal of Medical Case Reports)
Abstract Background Campylobacter is known to be the leading cause of foodborne illness. Campylobacter jejuni, specifically, most commonly causes self-limiting enterocolitis, but infection can lead to extraintestinal manifestations, including rare yet severe cardiac complications, such as myocarditis and/or pericarditis. This review aims to determine whether a relationship exists between the timing of a positive stool culture and the overall clinical course in patients with Campylobacter jejuni-associated myocarditis and/or pericarditis. Methods A systematic search was conducted using PubMed, MEDLINE, CINAHL Ultimate, Academic Search Premier, and Nursing and Allied Health Premium databases. A gray literature search was also performed. Covidence.org was used to screen, select, and extract data by two independent reviewers. Following a full-text evaluation, the quality of each study was assessed using the Joanna Briggs Institute Critical Appraisal Checklist for Case Reports. Results The search resulted in 434 records, of which 7 case reports met the inclusion criteria, each study including one patient. The average number of days from hospital presentation to obtaining a stool sample was 1.7. The average number of days from stool culture obtainment to clinical course improvement was 3.3, with four case studies reporting a range of 2–4 days. Conclusion This systematic review raises awareness regarding the manifestations of Campylobacter jejuni, specifically the severe cardiac symptoms that may present in young individuals. Given the significant sequelae that can develop, providers must elicit a thorough history consisting of questions related to recent travel, food consumption, and gastrointestinal symptoms, especially among young individuals presenting with cardiac complaints.